Phase II study on the efficacy and safety of Lapatinib administered beyond disease progression and combined with vinorelbine in HER-2/neu- positive advanced breast cancer: results of the CECOG LaVie trial - Thallinger, Christiane; Lang, Istvan; Kuhar, Cvetka Grasic; Bartsch, Rupert; Singer, Christian F; Petruzelka, Lubos; Melichar, Bohuslav; Knittelfelder, Regina; Brodowicz, Thomas; Zielinski, Christoph (BMC cancer, 2016)
BACKGROUND: Vinorelbine constitutes effective chemotherapy for metastatic breast cancer (MBC) and acts synergistically with trastuzumab in HER-2/neu positive disease. The present study was set out to evaluate the efficacy and safety of vinorelbine when combined with lapatinib, an anti-HER2 tyrosine-kinase inhibitor, as late-line regimen administered beyond previous disease progression on prior lapatinib in patients with HER-2/neu- positive MBC. METHODS: The CECOG LaVie study was designed as open-labeled, single-arm, multicenter phase II trial. Patients had to be pretreated with lapatinib plus chemotherapy, and received lapatinib at a daily dose of 1250 mg in combination with vinorelbine 20 mg/m(2) i.v. on days 1 and 8 of a three-week cycle until disease progression, intolerable toxicity or withdrawal of consent. Progression-free survival (PFS) was defined as primary study endpoint; secondary endpoints included overall survival (OS), response rate according to RECIST 1.1, and safety. The study was terminated early due to poor accrual. RESULTS: A total number of nine patients were included; lapatinib administered beyond disease progression combined with vinorelbine resulted in a median PFS of 7.7 months (95% CI 0.56-14.91) and a median OS of 23.4 months (95% CI 16.61-30.13), respectively. Partial remission was seen in one of nine patients, three patients had stable disease of > six months, whereas the remaining five patients had primary disease progression. In two patients, modification of vinorelbine dose due to toxicity became necessary; no dose modification was needed for lapatinib. The majority of reported adverse events (AE) were grade 1 and 2 in severity with diarrhea being the most commonly observed AE CONCLUSION: In this heavily pretreated patient population, combination of vinorelbine plus lapatinib showed encouraging activity and was characterized by an acceptable safety profile. Despite the low patient number, lapatinib plus vinorelbine may constitute a potential treatment option in heavily pretreated patients with HER-2/neu-positive MBC previously exposed to lapatinib. TRIAL REGISTRATION: EudraCT number 2009-016826-15, (15. 10.2009).
Keywords: dospělí; kombinovaná farmakoterapie; nádory prsu; Humans; Drug Therapy, Combination; lidé středního věku; Middle Aged; Antineoplastic Agents; chinazoliny; Vinblastine; Breast Neoplasms; protinádorové látky; Receptor, ErbB-2; vinblastin; receptor erbB-2; Adult; ženské pohlaví; Quinazolines; lidé; Aged; senioři; Female